Discovery and development of substituted thiadiazoles as inhibitors of Staphylococcus aureus Sortase A. Issue 19 (1st October 2019) - Wehrli, Patrick M.; Uzelac, Ivana; Olsson, Thomas; Jacso, Tomas; Tietze, Daniel; Gottfries, Johan
Graphical abstract: Abstract: High-throughput screening of small-molecule libraries has led to the identification of thiadiazoles as a new class of inhibitors against Staphylococcus aureus sortase A (SrtA). N-(5-((4-nitrobenzyl)thio)-1, 3, 4-thiadiazol-2-yl)nicotinamide (IC50  = 3.8 µM) was identified as a potent inhibitor of SrtA after synthetic modification of hit compounds. Additional ligands developed in this study displayed affinities in the low micromolar range without affecting bacterial growth in vitro . The study also suggest a new mode of action through covalent binding to the active site cysteine.